New stratigraphic and genetic model for the dolomitic cretaceous pinda reservoirs in angola part I-the pinda of angola, an integrated lithostratigraphic approach - Granier, Bruno [UNESP] (Society for Sedimentary Geology, 2017)
The Pinda Group of the Congo basin in the northern Angolan offshore is an overall transgressive supersequence of late Aptian-? early Cenomanian age. Due to synsedimentary salt tectonics of the underlying Loeme Salt, the original ramp arrangement is split into discrete structures corresponding to many proven, probable and possible oil and gas plays. Where the biostratigraphic information was not destroyed by pervasive dolomitization, the little that remains is not available to the general public because it is treated as proprietary data by the Sociedade Nacional de Combustíveis de Angola Empresa Pública-Sonangol E.P. Only a limited set of data containing lithostratigraphic information (e.g., some published well logs and photomicrographs of facies) is available. The aim of this paper is to give a little more information about the Pinda stratigraphy. For instance, to be formally defined, this poorly known unit required a type section, a shortcoming that is addressed here. The wireline log signatures of some regional seismic markers are documented because they are used to correlate wells and subdivide the Group into formations. The microfacies corresponding to some key electrofacies as well as the porosity types are also condensed in a microphotograph catalog. Finally, few examples of typical LoC (i.e., Line of Correlation) diagrams are displayed and interpreted.
Keywords: Albian; Angola; Cenomanian; Dolomite; Pinda; Reservoirs; Stratigraphy